Informing macroprudential policy choices using credit supply and demand decompositions - Claudio Barbieri; Cyril Couaillier; Cristian Perales; Costanza Rodriguez D'Acri (European Central Bank (ECB), 2022)
Macroprudential policies should strengthen the banking sector throughout the financial cycle. However, while bank credit growth is used to capture cyclical exuberance and calibrate buffer requirements, it depends on potentially heterogeneous dynamics on the borrower and lender sides. By decomposing credit growth into a common component and components capturing heterogeneity in supply and demand à la Amiti and Weinstein, 2018 applied on the euro area credit register ("AnaCredit"), we can inform the policy debates in two ways. Ex ante, we introduce a framework mapping the decomposition to different types of macroprudential instruments, specifically broad vs targeted measures. Ex post, we also show that the resulting decomposition can be used to assess the effectiveness of adopted measures on credit supply or demand. We find evidence that buffer releases and credit guarantees increased bank credit supply during the COVID-19 pandemic and interacted positively with banks' profitability.
Keywords: E58; E52; E44; G21; 330; Capital requirements; Bu er Releases; European Economy; Bank-lending channel; Credit Dynamics